MODIFYING SEX EXPRESSION OF PAPAYA (CARICA PAPAYA) THROUGH APPLICATION OF PLANT GROWTH REGULATORS - Higida, Catalino S; Pascual, Pet Roey L (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
Papayas are polygamous herbs having plants that produces flower but does not develop into fruits. Due to this condition, farmers have to plant up to five seedlings per hill if they process their own seeds or be forced to buy expensive F1 seeds from seed companies. Plant growth regulators play an important role in the sex expression of plants. Thus, a study was conducted to determine the effects of different plant growth regulators (Ethrel, Indole Butyric Acid and Kinetin) at different concentrations (50 ppm, 100 ppm and 200 ppm) on the sex ratio of papaya and the number of days for it to flower. Flowering of papaya ranged from 93 to 115 days from transplanting. Papaya plants applied with 100 ppm IBA at 0.25 ml per application (appearance of first to fourth true leaf) resulted to 108% more female flowers than those not applied with PGR. On the other hand, application of IBA at the same rate and concentration produced lesser hermaphrodite and male flowers at 10% and 3.33%, while those not applied with PGR produced 33.67% and 23.33%, respectively. This means that with the use of 100 ppm IBA, farmers will be able to process their own papaya seeds with higher chance of producing plants that will produce fruits. This, in turn, will reduce their dependency to multi-national seed companies as their sole source of papaya planting material.